Elevated urinary CRELD2 is associated with endoplasmic reticulum stress-mediated kidney disease - Kim, Yeawon; Park, Sun-Ji; Manson, Scott R; Molina, Carlos Af; Kidd, Kendrah; Thiessen-Philbrook, Heather; Perry, Rebecca J; Liapis, Helen; Kmoch, Stanislav; Parikh, Chirag R; Bleyer, Anthony J; Chen, Ying Maggie (JCI insight, 2017)
ER stress has emerged as a signaling platform underlying the pathogenesis of various kidney diseases. Thus, there is an urgent need to develop ER stress biomarkers in the incipient stages of ER stress-mediated kidney disease, when a kidney biopsy is not yet clinically indicated, for early therapeutic intervention. Cysteine-rich with EGF-like domains 2 (CRELD2) is a newly identified protein that is induced and secreted under ER stress. For the first time to our knowledge, we demonstrate that CRELD2 can serve as a sensitive urinary biomarker for detecting ER stress in podocytes or renal tubular cells in murine models of podocyte ER stress-induced nephrotic syndrome and tunicamycin- or ischemia-reperfusion-induced acute kidney injury (AKI), respectively. Most importantly, urinary CRELD2 elevation occurs in patients with autosomal dominant tubulointerstitial kidney disease caused by UMOD mutations, a prototypical tubular ER stress disease. In addition, in pediatric patients undergoing cardiac surgery, detectable urine levels of CRELD2 within postoperative 6 hours strongly associate with severe AKI after surgery. In conclusion, our study has identified CRELD2 as a potentially novel urinary ER stress biomarker with potential utility in early diagnosis, risk stratification, treatment response monitoring, and directing of ER-targeted therapies in selected patient subgroups in the emerging era of precision nephrology.
Keywords: Cardiac Surgical Procedures; Postoperative Complications; Cell Adhesion Molecules; uromodulin; Male; lidé; Humans; Podocytes; Child; Mutation; Extracellular Matrix Proteins; stres endoplazmatického retikula; Animals; podocyty; akutní poškození ledvin; nefrotický syndrom; Biomarkers; myši inbrední C57BL; zvířata; Uromodulin; mužské pohlaví; molekuly buněčné adheze; Mice, Inbred C57BL; dítě; Nephrotic Syndrome; Nephritis, Interstitial; biologické markery; pooperační komplikace; extracelulární matrix - proteiny; intersticiální nefritida; mutace; Acute Kidney Injury; Endoplasmic Reticulum Stress; kardiochirurgické výkony